Age-Dependent Dysregulation of APP in Neuronal and Skin Cells from Fragile X Individuals - Giulia Cencelli; Laura Pacini; Anastasia De Luca; Ilenia Messia; Antonietta Gentile; Yunhee Kang; Veronica Nobile; Elisabetta Tabolacci; Peng Jin; Maria Giulia Farace; Claudia Bagni (Cells, 2023)
Fragile X syndrome (FXS) is the most common form of monogenic intellectual disability and autism, caused by the absence of the functional fragile X messenger ribonucleoprotein 1 (FMRP). FXS features include increased and dysregulated protein synthesis, observed in both murine and human cells. Altered processing of the amyloid precursor protein (APP), consisting of an excess of soluble APPα (sAPPα), may contribute to this molecular phenotype in mice and human fibroblasts. Here we show an age-dependent dysregulation of APP processing in fibroblasts from FXS individuals, human neural precursor cells derived from induced pluripotent stem cells (iPSCs), and forebrain organoids. Moreover, FXS fibroblasts treated with a cell-permeable peptide that decreases the generation of sAPPα show restored levels of protein synthesis. Our findings suggest the possibility of using cell-based permeable peptides as a future therapeutic approach for FXS during a defined developmental window.